Medications and non-pharmacological measures to alleviate the symptoms of respiratory tract infections in the pediatric population - Tomić, Maja; Pecikoza, Uroš (Archives of Pharmacy, 2022)
In the pediatric population, acute respiratory tract infections (RTIs) are the most common reason for seeking professional help from a physician or a pharmacist. Alleviation of symptoms is the only therapeutic measure in viral RTIs and is an adjunct to antibiotic therapy in bacterial RTIs. This article discusses pharmacologic and non-pharmacologic options for treating nasal congestion, cough, fever and sore throat in RTIs and clinical evidence on their efficacy and safety in the pediatric population. In general, clinical studies conducted in children for most of these drug groups are few or nonexistent, making it difficult to create evidence-based recommendations. Nasal decongestants, cough suppressants, mucolytics, expectorants, antipyretics/analgesics and sore throat local preparations are available in suitable pharmaceutical forms and strengths for the certain age. As many of them are over-the-counter (OTC) preparations, it is necessary to strictly take into account the age of the child in whom they may be used and dose properly. Multicomponent preparations carry the risk of taking unnecessary medications and of their side effects. The use of multiple OTC medicines is associated with the risk of an overdose of a component that may be present in different preparations. Appropriate non-pharmacological measures (e.g. oral hydration, nasal saline application or irrigation, honey) may be helpful and should be used whenever possible due to their safety.
Keywords: respiratory tract infections, medications, non-pharmacological measures, pediatric population